The School-Based Jumat Berkah Program as a Reward-Based Strategy for Developing Students' Religious Character - Sheylla Putri Shafrilla; Dhita Ayomi Purwaningtyas (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
Developing students' religious character requires educational strategies that extend beyond religious instruction to foster the internalization of religious values through sustainable behavioral change. This study aims to examine the implementation of the school-based Jumat Berkah program as a reward-based strategy for developing students' religious character, analyze the role of rewards in facilitating religious character formation, and identify the supporting factors and challenges influencing the program's implementation at SMA Negeri 3 Pariaman. This study employed a descriptive qualitative approach using field research. Data were collected through participant observation, semi-structured interviews, and document analysis involving nine purposively selected informants, including the program initiator, an Islamic Religious Education teacher, homeroom teachers, and students. Data credibility was ensured through source and method triangulation, while data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that the Jumat Berkah program effectively develops students' religious character by integrating exemplary practices, religious habituation, positive reinforcement, and school culture. Rewards function primarily as initial positive reinforcement that encourages participation in religious activities before gradually facilitating the transition from extrinsically motivated behavior to intrinsically regulated religious commitment. The program also enhances students' worship consistency, social responsibility, discipline, and religious awareness. Its effectiveness is supported by teacher role modelling, continuous habituation, active involvement of the school community, and sustainable charity management, while uneven religious awareness, family and social environments, and technical constraints remain significant challenges. This study introduces an integrated perspective demonstrating that reward-based reinforcement functions as a transitional mechanism that supports the internalization of religious character through continuous habituation within school culture rather than merely encouraging short-term behavioral compliance. The study extends the application of behavioral reinforcement theory in Islamic education by proposing an integrated model that combines positive reinforcement, exemplary practices, religious habituation, and school culture as complementary strategies for sustainable religious character development.